(untitled) (Journal of the College of Basic Education, 2025)
This research aims to trace two of the most prominent thematic aspects in the poetry of the Andalusian poet Al-Sumaisir Khalaf bin Faraj Al-Albiri, who was famous for his scathing criticism of the Taifa kings in Andalusia, namely: asceticism and rebellion, and to compare these two aspects in his poetry by looking at the set of subjective and objective factors that embody the nature of the problematic relationship between the poet and his era. The close relationship between asceticism and rebellion is evident in Al-Sumaisir’s poetry in light of the prominent religious and moral reference in the poet’s positions, which made his rebellion and satire, on the one hand, and his tendency towards asceticism, on the other hand, have a prominent political character, revealing the political role in the manifestations of corruption that were prevalent in the poet’s era, especially on the religious, moral and social levels. Accordingly, the study came in two sections, the first of which dealt with the manifestations of asceticism in Al-Sumaisir’s poetry, and the second presented the manifestations of rebellion in Al-Sumaisir’s poetry. It is important to note that Al-Sumaisir’s poetry was not limited to topics of asceticism, rebellion, or satire, but rather expanded to include description, praise, and love poetry